HIV-Related Stigma, Frailty, and It’s Plausible Correlation: a Literature Review - Geraldino Hendy Manseaur; Iqbal Pramukti (Universitas Malahayati, 2026)
ABSTRACT Persons living with HIV experience many physical and non-physical health problems, despite the many interventions that have been made to improve the quality of life of PLWH. Some of the problems that are increasingly experienced by PLWH are frailty and stigmatization, and these two problems seem to have a relationship that affects the severity of each other. Further exploration of these two problems and their plausible correlation is needed to fill the gap in the knowledge that has never been discussed before. This scoping review aims to delve into what is known regarding HIV-related stigma, frailty, and their plausible correlation using the articles written in English and published in the last five years (2019-2024). The articles were acquired on August 2024 from various databases, namely, Springer Link, EBSCOhost, PubMed, ScienceDirect, Scopus, and Google Scholar. This review found that there’s an indirect correlation between HIV-related stigma and frailty through various pathways, such as, depression and social isolation. Overall, this scoping review underscores the need for a comprehensive, multidimensional approach to addressing the complex interplay between HIV-related stigma, frailty, and other social determinants of health. Interventions that target both the physical and psychosocial aspects of these issues may be crucial in improving the overall well-being and quality of life of people living with HIV. Keywords: HIV, Stigma, Frailty